Computer Science &Amp; Information Technology (CS &Amp; IT) 2021
DOI: 10.5121/csit.2021.110908
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Factors of Enabling I4.0 Technologies and Benefits in the Supply Chain

Abstract: Industry 4.0 technologies represent a new paradigm of integration of cyber-physical systems, information and communication solutions, with applications in many different domains. This topic has to date been vaguely explored in the realm of the social sciences; hence this study attempts to bridge this gap by investigating the challenges of innovation adoption, based on I4.0 technologies, more specifically the factors affecting adoption decisions. This paper, based on previous adoption literature, aims to identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The previous studies indicate that the i4.0 readiness can be tested statistically in a different dimension, but this study shows that the i4.0 readiness can be an important factor which may affect employee retention in some other but not as a moderator for the automotive industry (Samaranayake, Ramanathan and Laosirihongthong, 2018). Many previous studies have discussed management support as a moderator, indicating how it moderates investment, social capital, and i4.0 adoption (Franceli and Zilber Turri, 2021). The current statistical result does not support management support as a moderator between i4.0 adoption and training 4.0.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The previous studies indicate that the i4.0 readiness can be tested statistically in a different dimension, but this study shows that the i4.0 readiness can be an important factor which may affect employee retention in some other but not as a moderator for the automotive industry (Samaranayake, Ramanathan and Laosirihongthong, 2018). Many previous studies have discussed management support as a moderator, indicating how it moderates investment, social capital, and i4.0 adoption (Franceli and Zilber Turri, 2021). The current statistical result does not support management support as a moderator between i4.0 adoption and training 4.0.…”
Section: Resultsmentioning
confidence: 68%
“…(Prieto-Pastor and Martin-Perez, 2015; Barham et al, 2020). Management support is generally linked to the capability of management to figure out disparate employees' needs, arrange training that aligns with employees' jobs, manage the social relationship to engage employees enrolling in training programs, make someone feel valued, cared for and continue positive effect on others (Issah, 2018;Mohamad, Ismail and Nor, 2020) Management support can increase or decrease the adoption of new technology within an organisation (Franceli and Zilber Turri, 2021). Based on the previous work, the current study is supposed to test the moderating effect of management support between i4.0 adoption and training, positively impacting employee retention.…”
Section: Mediating Role Of Employee Competenciesmentioning
confidence: 99%
“…Tower. Exogenous variable for Cost of Technologies have observed variable as follows: investment risk which explain as projection of benefit cost analysis regarding this developing this system (Kfoury, 2021;Alacam et al 2021;Cichosz et al 2020;Chowdhury et al 2022), cost of training express as implementation cost to leverage user skills before use this system (Grover et al 2019;Miraz et al 2020;Choi et al 2020;Mkansi, 2021) and cost of operations talking about cost of development and stakeholders once running in daily business (Treiblmaier, 2018;Liotine, 2019;Marbouh et al 2020;Franceli et al 2021).…”
Section: )mentioning
confidence: 99%
“…Exogenous variable for Characters of Stakeholders have observed variable as follows: support from top management that talking about commitment that needed coming from leaders in each parties that involved (Sony et al 2019;Nuryyev et al 2020;Belinski et al 2020;Çolak et al 2022), organizations resistance express as potential response of discomfort behavior related transparency in operational or financial process (Cichosz et al 2020;Balci et al 2021;Baigy et al 2022), organization size talking about potential of adjustment of team involvement based on requirement of this system (Agostini et al 2019;Franceli et al 2021;Nuryyev et al 2020;Varriale et al 2021) and the last one is government regulation express as transaction method which need to harmonized related blockchain scheme (Ahmad et al 2020), (Min, 2019), (Syahchari et al 2022) Based on the above hypothesis, the researcher conducts a research model which will be running with Smart-PLS Software as shown in the Figure 1. There will be sign with rectangle on Figure 1 to express an exogenous, an endogenous variables and hypothesis of this research study.…”
Section: )mentioning
confidence: 99%
“…Moreover, researchers have reported differences in technological usage and adoption across industries (Kutnjak et al, 2019;Oh and Shim, 2020;Shrestha, 2021). Industries using IT systems have reported growth in operating profit margins and higher labor productivity (Bessen, 2017(Bessen, , 2020Franceli and Zilber Turri, 2021). The extant literature has shown that deploying IT and using IT knowledge in managing the supply chain is one of the prime success factors (Basheer et al, 2016;Nasiri et al, 2020).…”
Section: Techno-ethical Orientation and Ethical Decision-makingmentioning
confidence: 99%